2016
DOI: 10.1177/2047487316655452
|View full text |Cite
|
Sign up to set email alerts
|

Five-year hospitalisations and survival in patients admitted to inpatient cardiac rehabilitation after cardiac surgery

Abstract: The reduction in all-cause mortality at follow-up documented in those patients with severe disability post-surgery who improved after rehabilitation underscores the effectiveness of a comprehensive inpatient cardiac rehabilitation programme and should encourage a more widespread use of rehabilitation early after an acute cardiac event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Motoki et al [19] also reported that a low ADL status at discharge and poor improvement in ADL capacity during hospitalization predicted all-cause mortality after discharge in patients with acute decompensated heart failure; however, few previous studies have reported an association between ADL and prognosis in patients who underwent cardiovascular surgery. Marcassa et al [7] reported the BI to be a major predictor of survival and hospitalization during a 5-year follow-up in patients admitted for inpatient cardiac rehabilitation after cardiac surgery (mean age: 68 ± 11 years; time from surgery to inpatient cardiac rehabilitation admission: 9.7 ± 11.2 days).…”
Section: Discussionmentioning
confidence: 99%
“…Motoki et al [19] also reported that a low ADL status at discharge and poor improvement in ADL capacity during hospitalization predicted all-cause mortality after discharge in patients with acute decompensated heart failure; however, few previous studies have reported an association between ADL and prognosis in patients who underwent cardiovascular surgery. Marcassa et al [7] reported the BI to be a major predictor of survival and hospitalization during a 5-year follow-up in patients admitted for inpatient cardiac rehabilitation after cardiac surgery (mean age: 68 ± 11 years; time from surgery to inpatient cardiac rehabilitation admission: 9.7 ± 11.2 days).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on patients with cardiovascular disability accumulated in our Institute [15] showed that even when performing all these additional and IC types of procedures, the level of disability at discharge correlated with all-cause mortality.…”
mentioning
confidence: 87%
“…Patients that attended the most sessions tended to have the best outcomes; Shook et al reported significantly lower 180-day readmission rates post-discharge for subjects participating in Phase II CR ( 23 ). A longitudinal 5-year data analysis indicated that 75% of patients with severe disability were able to improve functional status and was associated with a 50% decrease in mortality ( 24 ).…”
Section: Pros and Cons Of Pac Settingsmentioning
confidence: 99%